Migrants' access to COVID-19 vaccination in Japan: Progress and challenges - Masami Fujita; Miwa Kanda; Hiroyuki Kiyohara; Saki Ikeda; Azusa Iwamoto; Kyoko Sudo; Yuko Teshima; Midori Nii; Yoji Murata; Jotaro Kato; Aiko Komatsu; Aya Yumino; et al. (Elsevier, 2023)
Objectives: This study aimed to review the progress and challenges of COVID-19 vaccine roll-out for migrants in Japan and discuss the approaches to address the challenges and better prepare for future waves of COVID-19 and other pandemics. Methods: We conducted a literature review using an assessment framework which we developed building upon existing frameworks and tools on access to health services and COVID-19 vaccination among migrants. Results: COVID-19 vaccination coverage among foreigners might be lower than that of nationals although the data on foreigners were not widely available. A gap appeared to exist between the government's efforts to disseminate vaccine-related information through multi-lingual websites and migrant communities as recipients. A series of barriers for migrants were identified at different stages of the vaccination process. While efforts were made by different units of local governments, NGOs, migrant communities, and international exchange associations, linkages across sectors and scaling-up appeared to be an issue. No foreigners were explicitly excluded from the entitlements of COVID-19 vaccination. The national level guidance, however, allowed sub-national levels to make a decision on whether or not undocumented foreigners should be reported to the immigration office or law enforcement when providing the services. In consequence, units in charge of public health and vaccination of some municipalities did not offer vaccination to those in need. Conclusion: Migrants, especially those unregistered face various barriers in accessing COVID-19 vaccination. It is critical to assess and address challenges concerning channels of information dissemination, pathways to access services, obstacles for vulnerable migrants, and data for evidence-based actions.